Witches & villains: the nasty tales - Dalldorf, Tamaryn (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My thesis compromises a variety of short stories which are modern re-writes of dark fairy tales. Fairy Tales often explore the dark side of human nature and in these stories I focus on the voices of female villains and the strange psychology which drives them. I find Fairy Tales absorbing because they reveal the vulnerabilities, dreams and fears of the human consciousness. My stories contain some satirical expositions of human nature and society. My influences are the anthology of short stories, "My mother She Killed Me and My Father He Ate Me" , The Grimm Fairy Tales (original) and The Fairy Tales of Charles Perrault as well as the writing of Horacio Moya, Angela Carter and Alissa Nutting for their dark satire and mockery of social eccentricities. Kate Bernheimer's "Form is Fairy Tale and Fairy Tale is Form" is very influential in terms of the style it recommends in writing such as: "every day magic" , "flatness" (a form of narration), abstraction and intuitive logic.
Keywords: South African fiction (English) -- 21st century; Short stories, South African (English) -- 21st century; Fairy tales -- 21st century